Dielectric, ferroelectric and optical properties of Na and Nb co-doped (Bi0.5Na0.5)0.94Ba0.06TiO3 - Ali, Asif; Zahid, Hina (Physics and Chemistry of Solid State, 2021)
[(Bi0.5Na0.5)0.94Ba0.06]1-xNaTi1-xNbO3 (x = 0.5 and 0.10) ceramics were prepared via conventional solid-state sintering route. X-ray diffraction analysis of the samples exhibited the formation of the cubic structure. Similar structure was observed from the Raman spectra of the samples. The optical band gap of the samples slightly decreased from 3.08 to 3.06 eV with increasing level of Na+ and Nb5+. The addition of Na+ and Nb5+ shifted Tm towards room temperature (RT). The sample x = 0.05 had a stable relative permittivity ɛr(mid) = 3914 across the temperature range 79-350 ℃ and tanδ < 0.025 (104-279 ℃). The energy density of sample with x = 0.05 was 0.4 J/cm3 which decreased to 0.32 J/cm3 at an applied electric field of 50 kV/cm with further substitution of Na+ and Nb5+ (i.e., x = 0.10).